Character Survey Assessment Instruments for Fifth Grade Elementary School Students - Wardana, I Wayan Raka; Rati, Ni Wayan (MIMBAR PGSD Undiksha, 2022)
The teacher's assessment of student character is only through direct observation of students without using an assessment instrument. In addition, students' behavior rarely reflects good and trustworthy character. This research aims to develop a character survey assessment instrument for fifth-grade elementary school students. This type of research is the development of the RDR model. The research subjects were two instrument experts and two practitioners. The product trial subjects consisted of 30 students. The methods used to collect data are questionnaires, interviews, documentation studies, and observations. The instrument used to collect data is a questionnaire. The data analysis techniques are descriptive, qualitative, and quantitative. The analysis results show that the experts' content validity of the character survey assessment instrument is 1.00 (very high). The teacher's content validity analysis results are 1.00 (very high). The experts' reliability test results are 1.00 (reliable), and the teacher is 1.00 (reliable). The results of the response analysis from the trial of the character survey assessment instrument were 95%. The character survey assessment instrument's criteria were very good based on the test results. It is concluded that the character survey instrument is suitable for use by teachers.